Water and mineral problems of the dromedary camel (an overview) - Farid M.F.A. (Séminaire sur la digestion, la nutrition et l'alimentation du dromadaire, 1989)
Water, heat and the associated salt problems can be detrimental to survival of desert animals. In this respect, the dromedary camel has always been legendary for its tolerance and adaptation to conditions of physiological and nutritional stress. It is the purpose of this article to first give an overview of the problems of maintaining heat and water balance under the adverse conditions of hot dry desert environments. Several topics are discussed to illustrate the peculiarities of the camel including the questions about its capacity to store heat and water and the adaptive mechanisms involved.
Séminaire sur la Digestion, la Nutrition et l'Alimentation du Dromadaire, 1988/02/27-1988/03/01, Ouargla (Algeria)